Do Patients with Multiple Sclerosis Derive More Benefit from Robot-Assisted Gait Training Compared with Conventional Walking Therapy on Motor Function? A Meta-analysis - Xie, Xiao; Sun, Hao; Zeng, Qing; Lu, Pengcheng; Zhao, Yijin; Fan, Tao; Huang, Guozhi (Frontiers in Neurology, 2017)
Objective: To determine whether robot-assisted gait training (RAGT) is more effective for improving mobility, endurance, gait performance and balance for patients with multiple sclerosis (MS) compared with conventional walking rehabilitation treatment (CWT). Data sources: Sources included the Cochrane Library, PubMed, Embase and Science Direct databases. Review method: All possible articles were retrieved by two independent investigators and relevant articles were gathered. Studies on adult patients (older than 19 years old) suffering from MS were included, regardless the subtype of MS diagnosis. Finally, we identified 7 studies that comprised 205 patients with MS. Results: We identified 7 studies comprising 205 patients with MS in our meta-analysis. The pooled mean difference for the six minutes’ walk test (6MWT) [MD (mean difference) 14.25, 95% CI (confidence interval) 3.19 to 25.32, Z=2.53, P=0.01, I²=54%], the P value is less than 0.05 which indicates that RAGT is superior to CWT for improving endurance among MS subjects. No significant improvement on using RAGT was found regarding the Berg Balance Scale (BBS) [MD= -0.59, 95% CI: -2.7 to 1.52, Z=0.55, P=0.58, I²=51%], ten-meter walk test (10MWT )[SMD (standard mean difference) =0.03, 95% CI: -0.26 to 0.31, Z=0.18, P=0.86, I²=48%] timed up and to go test (TUG) (MD= -1.04, 95% CI: -8.68 to 6.60, Z=0.27, P=0.79), or stride length (SL) (SMD= 0.36, 95% CI: -0.13 to 0.85, Z=0.73, P=0.15). Conclusion: We can conclude that RAGT can bring more benefits on improving 6MWT among MS patients, but it’s not enough to make a clinical significance conclusion. It takes reservations about recommending all MS patients to take RAGT as primary rehabilitation intervention. Except patients with severe MS and wants to participate in gait function rehabilitation training in the early stage of this disease.